Strategi Bauran Pemasaran Syariah (Studi Kasus Sayuran Hidroponik Hani Farm Samarinda) - Darmawati Darmawati; Alias Chandra; Muhammad Irfan Zainal Efendi (Borneo Islamic Finance and Economics Journal, 2023)
The 7P marketing mix strategy is a combination of product, price, promotion, place, people, physical evidence, and process. In each mix has a role to succeed in marketing achievements. In every important marketing mix strategy implemented based on sharia marketing. Hani Farm was founded in 2019 and is a producer of hydroponic vegetables that are cultivated and managed by Islamic boarding schools where students play an active role. Hani Farm was also identified as using a marketing mix strategy, with increased turnover even though there was a decrease when PPKM occurred so it is important to study the marketing mix strategy of Hani Farm Samarinda from a sharia marketing perspective. The research method is qualitative research. Data collection techniques through observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, then drawing conclusions. Based on the results of Hani Farm Samarinda's marketing mix research from a sharia marketing perspective; Hani Farm's products are vegetables and vegetable delivery services. The price of vegetable products is determined based on market prices and service product tariffs using the average rate in one area of ​​Samarinda City. Promotion is done by sales promotion, publicity, and personal selling. The place is located at the KH Harun Nafsi Islamic boarding school which has easy access to consumers. Human resources are equipped with knowledge and coaching and are supervised by field coordinators at work. The process is carried out following standard rules and the ordering process is made easy to understand and work on. In the marketing mix strategy, Hani Farm has carried it out with sharia marketing values, namely shiddiq, amanah, fathanahtabligh and. As well as the principles of sharia marketing, namely strategy, needs, halal, welfare, and mutual agreement. And the characteristics of sharia marketing are theistic, ethical, realistic, and humanistic.